A writing workshop model to enhance students’ skills in writing essays in Sundanese - Usep Kuswari; Ruswan Dallyono (Indonesian Journal of Applied Linguistics, 2022)
Writing is difficult. Having a limited understanding on what to write or the fear of getting grammar or spelling errors is often a major problem for students when they are instructed to write something, be it an essay or an article.  Such difficulties are respective for Sundanese language classes in West Java. The study reported in this paper aims to investigate a number of fundamental problems of writing in Sundanese classes at a Junior High School. The study seeks to address the problems in the area of teaching writing in Sundanese classes by providing a comprehensive picture of the practice of a writing workshop model in the selected class. The study is classroom action research taking place in a public Junior High School in West Java, specifically in a Sundanese language class. The participants of the study were 36 students of 9th grade (comprising 14 male students and 22 female students) in 2018-2019 academic years. There were 3 cycles involved in this action research implemented throughout a semester. The study revealed that the use of the writing workshop model in teaching writing in Sundanese could improve the students’ writing skills. The writing workshop model, which focused on personal analysis and peer-feedback in the essay writing process, facilitated 9th grade students in producing, evaluating, and presenting essays within their respective groups. A supportive social environment in groups allowed for students’ enjoyment in writing. This environment thus led students to be exposed to varied topics and linguistic expressions in multi-social contexts. This study suggests that there are potential benefits from implementing the writing workshop model in the practice of teaching writing. Therefore, language teachers are suggested that they should apply this model in their teaching of writing. Through this model, students will be more engaged in their writing classes and learn writing in more meaningful, fun, creative, and dialogic ways.